Efektivitas Teknik SLA (Structured Learning Approach) untuk Meningkatkan Penyesuaian Diri Siswa Prakerin di Lingkungan Universitas Kanjuruhan Malang - Leny Latifah (Universitas Kanjuruhan Malang, 2015)
The development of technology that so fast and orientation nasional-internasional broad organization, requires employement has high competence. The organization of employement certainly create a new situation and put school graduates to be able to conform to the situation change. Self Adjustment is constantly interaction between individuals with him, with others, and with the environment. Self Adjustment, help students become happy and Able to devote attention and affection to the people. On the other hand , when individual unable to meet suit in work environment and he will experience conflict the inner and not optimal to his advantage. Structured Learning Approach is an approach learn structured developed based on theoretical social learning and modification behavior. This study used an experimental research design which aims to determine the effectiveness of SLA in increasing self adjustment in the working environment for students Prakerin in groups. Research subjects is 14 students prakerin at the university of kanjuruhan. The instrument used self adjustment scale developed by researchers.The research results show that (1) the average value of the pretest students before training is 32.07, (2) The average value of posttest students after the training 103.79, (3) 14 respondents have higher scores after the training than before the training, (4) the average increase after post-test was 7.50 with a significance level of 0.001.